2014
DOI: 10.1186/1471-2466-14-60
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of whole body vibration training in patients hospitalised for COPD exacerbations - a randomized clinical trial

Abstract: BackgroundPatients with stable COPD show improvements in exercise capacity and muscular function after the application of whole body vibration. We aimed to evaluate whether this modality added to conventional physiotherapy in exacerbated hospitalised COPD patients would be safe and would improve exercise capacity and quality of life.Methods49 hospitalised exacerbated COPD patients were randomized (1:1) to undergo physiotherapy alone or physiotherapy with the addition of whole body vibration. The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 38 publications
(30 reference statements)
2
109
0
8
Order By: Relevance
“…Reduced parameters of heart rate variability were improved [34]. It is suggested that these mechanisms contribute to beneficial prognostic effects of controlled rehabilitation programs in COPD [26,55,56]. Reduction of increased ventricular wall stress should be envisaged as treatment target.…”
Section: Copd and Increased LV Wall Stressmentioning
confidence: 93%
“…Reduced parameters of heart rate variability were improved [34]. It is suggested that these mechanisms contribute to beneficial prognostic effects of controlled rehabilitation programs in COPD [26,55,56]. Reduction of increased ventricular wall stress should be envisaged as treatment target.…”
Section: Copd and Increased LV Wall Stressmentioning
confidence: 93%
“…A subgroup analysis provided evidence that the improvement in mMRC scale score was less pronounced in patients entering pulmonary rehabilitation within 2 weeks after another hospital stay (most likely COPD exacerbation). This may be due to the fact that hospital-based treatment of an exacerbation had already led to a significant improvement of dyspnea [20] and quality of life [21] and further improvement would be difficult to achieve. Furthermore, the Borg scale score decreased despite an increasing 6-MWT distance, suggesting that at an equal distance the Borg scale score would have been even better.…”
Section: Discussionmentioning
confidence: 99%
“…Although WBVT is not a new approach in medical exercise therapy there is only a scarce number of studies currently available that investigated WBVT in patients with chronic respiratory diseases like chronic obstructive pulmonary disease (COPD) [7][8][9]. However, a recently published systematic review [10] has summarized that there seems to be a conclusive tendency that WBVT may be an effective and promising additional exercise method beyond traditional training regimes in patients with COPD to increase functional exercise capacity .…”
Section: Introductionmentioning
confidence: 97%